2015
DOI: 10.1038/ni.3093
|View full text |Cite
|
Sign up to set email alerts
|

The long intergenic noncoding RNA landscape of human lymphocytes highlights the regulation of T cell differentiation by linc-MAF-4

Abstract: Long non-coding-RNAs are emerging as important regulators of cellular functions but little is known on their role in human immune system. Here we investigated long intergenic non-coding-RNAs (lincRNAs) in thirteen T and B lymphocyte subsets by RNA-seq analysis and de novo transcriptome reconstruction. Over five hundred new lincRNAs were identified and lincRNAs signatures were described. Expression of linc-MAF-4, a chromatin-associated TH1-specific lincRNA, was inversely correlated with MAF, a TH2-associated tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
274
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 301 publications
(280 citation statements)
references
References 53 publications
4
274
0
2
Order By: Relevance
“…Distance of lncRNA TSS to FANTOM CAGE peak (log10(bp)) Previous studies in the T-cell lineage had shown that intergenic lncRNA expression is highly restricted even between closely related T-cell subsets. 17 For personal use only. For personal use only.…”
Section: Chromatin Signatures Identify Intergenic Lncrnas With Enhancmentioning
confidence: 98%
See 1 more Smart Citation
“…Distance of lncRNA TSS to FANTOM CAGE peak (log10(bp)) Previous studies in the T-cell lineage had shown that intergenic lncRNA expression is highly restricted even between closely related T-cell subsets. 17 For personal use only. For personal use only.…”
Section: Chromatin Signatures Identify Intergenic Lncrnas With Enhancmentioning
confidence: 98%
“…This is a consequence of the expression patterns of lncRNAs, which are often restricted to 1 or very few tissues or cell types. 9 Recent studies have addressed this limitation by surveying lncRNA expression in several organisms and tissues, [13][14][15][16][17] including murine T cells 18 ; however, there have been no comparable attempts to use sequencing technologies to describe the murine B-cell lncRNA repertoire.…”
Section: Introductionmentioning
confidence: 99%
“…MAF plays multiple roles in regulation of cellular development and differentiation[65]. Moreover, interaction between long intergenic non-coding RNAs (lincRNAs, linc-MAF-4) and MAF involves in the T lymphocyte differentiation[66]. In addition, an lncRNA-MAF transcription factor network plays an essential role in epidermal differentiation[67].…”
Section: Discussionmentioning
confidence: 99%
“…MAF кодирует транскрипционный фактор, вовлеченный в дифференцировку Th2-клеток, а также превраще-ние мезенхимальных стволовых клеток в остеобласты или адипоциты [13]. MAF также требуется для эффектив-ного развития Th17 клеток [14]. MAF входит в подкласс bZIP факторов с основным доменом типа «лейцино-вая застежка».…”
Section: Discussionunclassified